Test–retest reliability of a simple bedside-quantitative sensory testing battery for chronic neuropathic pain. (13th January 2023) - Sachau, Juliane; Appel, Christina; Reimer, Maren; Sendel, Manon; Vollert, Jan; Hüllemann, Philipp; Baron, Ralf
Abstract : Supplemental Digital Content is Available in the Text. In addition to the previously described good criterion validity, most bedside-quantitative sensory testing parameters showed satisfactory test–retest reliability and divergent validity, allowing their use in clinical practice/studies. Abstract: Introduction: The sensory phenotype is believed to provide information about the underlying pathophysiological mechanisms and to be used in the diagnosis and treatment of chronic neuropathic pain. However, the use of standardized quantitative sensory testing (QST) protocols is limited due to high expenditures of time and costs. Thus, a simple bedside-QST battery was recently developed showing good agreement when compared with laboratory QST. The aim of this study was to preliminary validate this bedside-QST protocol. Methods: Patients experiencing chronic pain with neuropathic features (n = 60) attended 3 visits. During the first visit, laboratory QST and bedside-QST were performed by the same trained investigator. Three hours and 3 weeks later, bedside-QST was repeated. Patients completed questionnaires regarding their pain (intensity, quality), depression/anxiety, and quality of life. Test–retest reliability and convergent/divergent validity were investigated. Results: Most of the bedside-QST parameters, including also those recommended in our first study as being indicative for sensory phenotypes, revealed a moderate to excellent test–retest reliability. Overall, results for short-term reliability and interval-scaled parameters were slightly better. Most of the bedside-QST parameters did not correlate with the depression and anxiety score, suggesting a good divergent validity. Conclusions: Bedside-QST has good criterion and divergent validity as well as reliability. This battery consists of 5 low-cost devices that can be quickly and easily used to characterize the sensory phenotype of patients with neuropathic pain. A combination of bedside-QST parameters can be used to investigate patients' subgroups with specific pathophysiological mechanisms and to identify treatment responders.